Microbiota profiles in pre-school children with respiratory infections: Modifications induced by the oral bacterial lysate OM-85 - Esposito, Susanna; Ballarini, Stefania; Argentiero, Alberto; Ruggiero, Luca; Rossi, Giovanni A.; Principi, Nicola (Frontiers in Cellular and Infection Microbiology, 2022)
To describe microbiota profiles, identify signs of dysbiosis associated to rRTIs and the potential association between OM-85 clinical efficacy and the effects on bacterial commensals, we analysed gut and nasopharynx (NP) microbiome composition in pre-school children with history of RTIs included in the OM-85-Pediatric rRTIs (OMPeR) clinical trial (https://www.clinicaltrialsregister.eu/ctr-search/trial/2016-002705-19/IT) . Relative percentage abundance was used to describe microbiota profiles in all the available biological specimens, grouped by age, atopy and rRTIs at both inclusion (T0) and at the end of the study, after treatment with OM-85 or placebo (T1). At T0, Firmicutes and Bacteriodetes were predominant genera in gut and Proteobacteria, Firmicutes, and Actinobacteria in NP samples. Gut microbiota relative composition differed with age (<2 vs >2 yrs) for Firmicutes, Proteobacteria, Actinobacteria, Ruminococcus spp. and Bifidobacterium spp. (p<0.05). Moraxella was more enriched in the NP of patients with history of up to 3 RTIs. Intra-group changes in relative percentage abundance were described only for patients with gut and NP microbiota analysis available at both T0 and T1 for each study arm. In this preliminary analysis, the gut microbiota seemed more stable over 6-month study in the OM-85 group, whose mean age was lower, as compared to the placebo group (p=0.004). In this latter group, the relative abundance of Bacteroides decreased significantly in children ≥2 yrs. Some longitudinal significant differences in genera relative abundance were also detected in children of ≥ 2 yrs for NP Actinobacteria, Haemophilus, Corynebacterium in the placebo group only. Due to the small number of patients in the different sub-populations, we could not identify significant differences in the clinical outcome and therefore no associations with microbiota changes were searched. The use of bacterial lysates might play a role in modulating dysbiosis, but further data and advanced analysis are needed to prove this in less heterogenous populations with higher numbers of samples considering the multiple influencing factors such as delivery method, age, environment, diet, antibiotic use, and type of infections to ultimately show any associations with prevention of rRTIs.